Association of metformin and statin medications with surrogate measures of cardiovascular disease in youth with type 1 diabetes: the SEARCH for diabetes in youth study - Evgenia Gourgari; Jeanette M. Stafford; Ralph D'Agostino Jr; Lawrence M. Dolan; Jean M. Lawrence; Amy Mottl; Catherine Pihoker; Elaine M. Urbina; R. Paul Wadwa; Dana Dabelea (Korean Society of Pediatric Endocrinology, 2019)
Purpose Youth with type 1 diabetes mellitus (T1DM) are at risk of cardiovascular disease (CVD). We evaluated if metformin or statin use was associated with surrogate measures of improved CVD. Methods We included participants from the SEARCH observational study. Participants treated with insulin plus metformin (n=42) or insulin plus statin (n=39) were matched with 84 and 78 participants, respectively, treated with insulin alone. Measures of arterial stiffness obtained were pulse wave velocity (PWV), augmentation index (AI75), and heart rate variability as standard deviation of the normal-to-normal interval (SDNN) and root mean square differences of successive NN intervals (RMSSD). Results CVD measures were not significantly different among participants on insulin plus metformin versus those on insulin alone: PWV (5.9±1.0 m/sec vs. 5.8±1.5 m/sec, P=0.730), AI75 (1.8 [-6.0 to 8.0] vs. -2.4 [-10.7 to 3.8], P=0.157), SDNN (52.4 [36.8-71.1] m/sec vs. 51.8 [40.1-74.9] m/sec, P=0.592), and RMSSD (43.2 [29.4-67.6] vs. 47.4 [28.0-76.3], P=0.952). CVD measures were not different for statin users versus nonusers: PWV (5.7±0.8 m/sec vs. 5.9 ±1.1 m/sec, P=0.184), AI75 ( -4.0 [-9.5 to 1.7] vs. -6.7 [-11.3 to 5.7], P=0.998), SDNN (54.6 [43.5-77.2] m/sec vs. 63.1 [44.2-86.6] m/sec, P=0.369), and RMSSD (49.5 [31.2-74.8] vs. 59.2 [38.3-86.3], P=0.430). Conclusions We found no associations of statin or metformin use with surrogate measures of CVD. Future prospective pediatric clinical trials could address this issue.